KONSEP MARGIN, UJRAH DAN BAGI HASIL DALAM EKONOMI SYARIAH - Latifah, Eny; Abdullah, Rudi; Adnan Hakim, Al Asy Ari (JITAA : Journal Of International Taxation, Accounting And Auditing, 2022)
The aim of this research is to understand the concept of ujrah, profit sharing and margin as applied in sharia economics. The research method used is descriptive qualitative with a type of literature. The research results show that the concepts of ujrah, margin and profit sharing are in line with Stewardship Theory. The profit-loss sharing system is a system of sharing business results (profits and losses) which are divided based on a ratio (nisbah) in the form of a percentage and agreed upon at the beginning of the contract. The Profit Sharing System is divided into 2, namely profit sharing and Revenue Sharing. Profit Sharing has 2 (two) treatments, namely: Profit Sharing mechanism, and Profit and loss sharing mechanism. Profit margins are set flexibly and can be determined annually, daily or monthly. Margin recognition can be calculated using 4 methods, namely: (1) Sliding profit margin method: (2) Average profit margin; (3) Flat profit margin; (4) Annuity Profit Margin. Ujrah/Fee is a reward given by a service user as a form of exchange for the services/benefits provided by the service provider in an ijarah (lease) agreement